2022
DOI: 10.3389/fonc.2022.836511
|View full text |Cite
|
Sign up to set email alerts
|

P4HA1 Regulates CD31 via COL6A1 in the Transition of Glioblastoma Stem-Like Cells to Tumor Endothelioid Cells

Abstract: Glioblastoma multiforme (GBM) is a common intracranial malignancy characterized by abundant and aberrant vasculature. The efficiency of existing antivascular treatments remains unsatisfactory. The transition of glioblastoma stem-like cells (GSCs) into tumor endothelioid cells (ECs) has been thought to cause glioma neovascularization and anti-angiogenesis tolerance, but the mechanisms regulating glioma transdifferentiation remains unclear. Our previous study found that P4HA1 regulates GSCs vascular mimicry in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
7
0
3
Order By: Relevance
“…COL6A1 and the vascular endothelial molecular marker cluster of differentiation 31 (CD31) showed positive correlations in in vivo assays. Alterations in the expression of COL6A1 and CD31 induced glioma angiogenesis (Han et al, 2022). Additionally, physical compaction of human GBM cell lines U87MG, U251, and LN229 induced the expression of collagen VI and the collagen crosslinking enzyme lysyl oxidase, and upregulated the expression of the angiogenic factor VEGF (Mammoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…COL6A1 and the vascular endothelial molecular marker cluster of differentiation 31 (CD31) showed positive correlations in in vivo assays. Alterations in the expression of COL6A1 and CD31 induced glioma angiogenesis (Han et al, 2022). Additionally, physical compaction of human GBM cell lines U87MG, U251, and LN229 induced the expression of collagen VI and the collagen crosslinking enzyme lysyl oxidase, and upregulated the expression of the angiogenic factor VEGF (Mammoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A subpopulation of glioblastoma-derived ECs harbours the same somatic mutations (for example, mutation in the gene encoding EGFRvIII and chromosome 7 amplification) as GSCs, indicating that a notable portion of the vascular endothelium has a neoplastic origin and GSCs can transdifferentiate into functional ECs, thereby contributing to tumour vascularization 20 , 21 , 205 . Recently, the P4HA1–COL6A1 axis was identified as a modulator of GSC-to-EC transdifferentiation 206 . Additional candidate modulators of this process include ETV2, a master regulator of EC development, and the transcription regulator TWIST1, and their expression positively correlates with malignancy grade 207 , 208 .…”
Section: Angiogenesis In Brain Tumoursmentioning
confidence: 99%
“…Furthermore, Hu et al demonstrated that GSC transdifferentiation into GdECs is mediated by the epigenetic activation of Wnt5a, through Akt signaling, and promotes host EC recruitment to create a vascular niche sustaining GSC growth and survival [ 120 ]. Recently, it has been reported that the P4HA1/COL6A1 signal axis can drive the transdifferentiation of GSCs into GdECs, promoting the expression of the endothelial marker CD31, thus contributing to the neovascularization process in response to the hypoxic microenvironment [ 121 ]. The authors also showed the co-expression of P4HA1 and CD31 in endothelial cells within blood vessels in human glioma specimens, other than a positive correlation between P4HA1 and the blood vessel density [ 121 ].…”
Section: Gbm-associated Mechanisms Of Neovascularizationmentioning
confidence: 99%
“…Recently, it has been reported that the P4HA1/COL6A1 signal axis can drive the transdifferentiation of GSCs into GdECs, promoting the expression of the endothelial marker CD31, thus contributing to the neovascularization process in response to the hypoxic microenvironment [ 121 ]. The authors also showed the co-expression of P4HA1 and CD31 in endothelial cells within blood vessels in human glioma specimens, other than a positive correlation between P4HA1 and the blood vessel density [ 121 ].…”
Section: Gbm-associated Mechanisms Of Neovascularizationmentioning
confidence: 99%
See 1 more Smart Citation